The Relationship Between Internal Locus of Control and Students Entrepreneurship Interest of SMK Negeri 2 Bukittinggi - Azzahra, Tassania Ridho; Yulastri, Asmar; Fridayati, Lucy; Gusnita, Wiwik (Universitas Negeri Padang, 2023)
The research background is the low entrepreneurship interest for students majoring in Culinary at SMK Negeri 2 Bukittinggi. It is assumed because students feel insecure and afraid of failure to open a business. The research purpose is to describe 1) students' internal locus of control, 2) students' entrepreneurship interest, and 3) analyze the relationship between internal locus of control and students' entrepreneurship interest. This type of research uses quantitative methods with a correlational approach. The population of the study was 106 students of class XII Culinary at SMK Negeri 2 Bukittinggi. The research sample 51 people selected by Proportionate Random Sampling. The data collection by questionnaire distributed via the Google form. Data analysis used descriptive analysis and correlational analysis. The results showed that: 1) the level of internal locus of control was in the medium category with a range of 46.2 - 58.8 (51%), 2) the level of entrepreneurship interest was in the low category with a range of 34.4 - 52.8 (47,1%), 3) there was positive and significant relationship between internal locus of control and entrepreneurship interest with a correlation value of rxy 0.628 which is considered strong and Tcount (5.452) > Ttable (2.010). This means that if the internal locus of control is low, the entrepreneurship interest is also low, conversely, the higher the internal locus of control, the higher the student's entrepreneurship interest.